Metalation of Olefinic Positions in Norbornadiene: Enhancement and Attenuation of Kinetic CH-Acidities by a Neighboring Enesilane Moiety - Alessandro Mordini; Manfred Schlosser (CHIMIA)
When treated with butyllithium in the presence of sodium or potassium tert-butoxide, 2-trimethylsilyl- and 2-triethylsilyl-norbornadiene undergo hydrogen/metal-exchange mainly at the 5-position. The latter position is found to be slightly activated relative to unsubstituted norbornadiene while the two other olefinic positions prove to be quite inert. Two side reactions are observed: the metalation of silicon-attached methyl groups and the replacement of the entire trialkylsilyl group by a metal atom.